Prognostic significance of 2-hydroxyglutarate levels in acute myeloid leukemia in China - Wang, Jiang-Han; Chen, Wen-Lian; Li, Jun-Min; Wu, Song-Fang; Chen, Tian-Lu; Zhu, Yong-Mei; Zhang, Wei-Na; Li, Yang; Qiu, Yun-Ping; Zhao, Ai-Hua; Mi, Jian-Qing; Jin, Jie; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
The 2-hydroxyglutarate (2-HG) has been reported to result from mutations of isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) genes and to function as an “oncometabolite.” To evaluate the clinical significance of serum 2-HG levels in hematologic malignancies, acute myeloid leukemia (AML) in particular, we analyzed this metabolite in distinct types of human leukemia and lymphoma and established the range of serum 2-HG in appropriate normal control individuals by using gas chromatograph–time-of-flight mass spectrometry. Aberrant serum 2-HG pattern was detected in the multicenter group of AML, with 62 of 367 (17%) patients having 2-HG levels above the cutoff value (2.01, log ₂-transformed from 4.03 μg/mL). IDH1/2 mutations occurred in 27 of 31 (87%) AML cases with very high 2-HG, but were observed only in 9 of 31 (29%) patients with moderately high 2-HG, suggesting other genetic or biochemical events may exist in causing 2-HG elevation. Indeed, glutamine-related metabolites exhibited a pattern in favor of 2-HG synthesis in the high 2-HG group. In AML patients with cytogenetically normal AML (n = 234), high 2-HG represented a negative prognostic factor in both overall survival and event-free survival. Univariate and multivariate analyses confirmed high serum 2-HG as a strong prognostic predictor independent of other clinical and molecular features. We also demonstrated distinct gene-expression/DNA methylation profiles in AML blasts with high 2-HG compared with those with normal ones, supporting a role that 2-HG plays in leukemogenesis.